2021
DOI: 10.1016/j.heliyon.2021.e08578
|View full text |Cite
|
Sign up to set email alerts
|

The farming management of Dayak People's community based on local wisdom ecosystem in Kalimantan Indonesia

Abstract: This research aims to explain the urgency of the customary values and traditions in the farming management system of the Dayak People's in Kalimantan. The approach used was Kroeber and Kluckhohn (1952) in relation with the cultural cycle. This approach is important to explain the cycle of farming management systems and their concept about nature and environment in Dayak community. In the farming context, various existing values in Dayak community has been found such as values containing togetherness, compassio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 21 publications
0
27
0
4
Order By: Relevance
“…The existence of adherence to local knowledge has a positive impact on the biodiversity of the Ngerong Cave area. Similar research carried out in the karst water sources in the Tulungagung area and agricultural regions of the Dayak tribe in Kalimantan showed that local wisdom could maintain ecosystems and a sustainable environment (Kurniawati et al, 2020;Murhaini & Achmadi, 2021) Further interviews with caretakers and community leaders, as well as some respondents, said they had heard word-of-mouth or folklore stories that there was a past incident that caused someone to die from taking Bader fish and bats in the Ngerong Cave area. These stories further make the community and tourists in the Ngerong Cave area believe that what is in the Ngerong Cave area must be maintained and protected.…”
Section: Finding and Discussionmentioning
confidence: 86%
“…The existence of adherence to local knowledge has a positive impact on the biodiversity of the Ngerong Cave area. Similar research carried out in the karst water sources in the Tulungagung area and agricultural regions of the Dayak tribe in Kalimantan showed that local wisdom could maintain ecosystems and a sustainable environment (Kurniawati et al, 2020;Murhaini & Achmadi, 2021) Further interviews with caretakers and community leaders, as well as some respondents, said they had heard word-of-mouth or folklore stories that there was a past incident that caused someone to die from taking Bader fish and bats in the Ngerong Cave area. These stories further make the community and tourists in the Ngerong Cave area believe that what is in the Ngerong Cave area must be maintained and protected.…”
Section: Finding and Discussionmentioning
confidence: 86%
“…Salah satunya adalah Karinding. Karinding adalah salah satu bentuk karya seni bangsa Indonesia yang memiliki bentuk dan bunyi yang khas (Murhaini, 2021). Karinding adalah alat musik perkusi yang digunakan oleh para karuhun untuk mengusir hama di sawah, bunyinya yang low decible sangat merusak konsentrasi hama.…”
Section: Pendahuluanunclassified
“…Jaha kec. Balaraja (Kuitert, 2020;Murhaini, 2021;Punpeng, 2020). Karinding sangat lekat dalam kegiatan masyarakatnya sejak lama.…”
Section: Hasil Dan Pembahasan Karinding Khas Balaraja DI Kampung Jaha...unclassified
“…The social dimension is found at each stage of farming which is reflected in the mutual cooperation of the residents at all stages of farming known as handep. (Murhaini & Achmadi, 2021). Unfortunately, farming practices are currently constrained by the large number of oil palm and mining companies buying land use rights.…”
Section: Farmingmentioning
confidence: 99%